(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
Complex comparative analysis of building energy performance rates in EU countries and Ukraine has been carried out. The relation between building insulation rates and European countries climate condition has been investigated. It is illustrated that there is a significant gap between building energy efficiency characteristics in Ukraine and in most of the EU countries. Economically justified rates of building envelope heat exchange resistance which can lead Ukraine to common European level based on optimized calculations are suggested. The necessity for further increase in building envelope heat exchange resistance rates in order to raise building energy efficiency and put Ukrainian building regulations in harmony with EU countries corresponding norms is proved.